(untitled) (IIUC Studies, 2009)
Now a days e-commerce and e-payments plays a great role to enhance business policies as well as our life style. I have studied both conventional and Islamic perspective of e-commerce and e-payments procedures. In Islam pay in advance is allowed with certain conditions. So I proposed a method of e-commerce and e-payments which is permissible by Islamic shariah. Muslims also can take the advantages of those modern policies if we can adjust the procedures with the teachings of Islam. Doi: IIUC Studies Vol.2 2004 Â